2016
DOI: 10.1002/lary.25937
|View full text |Cite
|
Sign up to set email alerts
|

Epitympanum volume and tympanic isthmus area in temporal bones with retraction pockets

Abstract: NA Laryngoscope, 126:E369-E374, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…The persistence of otitis media or of negative pressure in the middle ear is the basis of the development of complications, such as cholesteatoma ( Charachon et al., 1992 ). Negative middle ear pressure can be created by a selective dysventilation of the epitympanum, which is typically smaller in patients with RPs ( Monsanto et al., 2016 ); Besides, a large mastoid antrum can contribute to a fall of pressure behind the TM ( Grewal et al., 2003 ). Marchioni et al.…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of otitis media or of negative pressure in the middle ear is the basis of the development of complications, such as cholesteatoma ( Charachon et al., 1992 ). Negative middle ear pressure can be created by a selective dysventilation of the epitympanum, which is typically smaller in patients with RPs ( Monsanto et al., 2016 ); Besides, a large mastoid antrum can contribute to a fall of pressure behind the TM ( Grewal et al., 2003 ). Marchioni et al.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the incidence of acute otitis media is 10.85%, accounting for over 709 million new cases every year . It is associated with several acute complications and long‐term sequelae, which include hearing loss, delayed speech and neurologic development, tinnitus, and dizziness .…”
Section: Introductionmentioning
confidence: 99%
“…8 Regarding the COM groups, studies have reported increased degrees of dysventilation to the epitympanum in temporal bones with RPs than ears without RPs; thus, COM bones with RPs are included in a higher severity degree than COM without RPs. 10 The presence of cholesteatoma is the ultimate stage of the continuum of otitis media. It is associated with more severe destruction and mucosal changes in the middle ear cleft, features that are less frequently observed in cases of COM without cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal bones from donors who had CF usually do not have pathologic changes in the middle ear cleft . Regarding the COM groups, studies have reported increased degrees of dysventilation to the epitympanum in temporal bones with RPs than ears without RPs; thus, COM bones with RPs are included in a higher severity degree than COM without RPs . The presence of cholesteatoma is the ultimate stage of the continuum of otitis media.…”
Section: Methodsmentioning
confidence: 99%